Characterization of Neonatal Vocal and Motor Repertoire of Reelin Mutant Mice - Romano, Emilia; Michetti, Caterina; Caruso, Angela; Laviola, Giovanni; Scattoni, Maria Luisa (PloS one, 2013)
Reelin is a large secreted extracellular matrix glycoprotein playing an important role in early neurodevelopment. Several genetic studies found an association between RELN gene and increased risk of autism suggesting that reelin deficiency may be a vulnerability factor in its etiology. Moreover, a reduced reelin expression has been observed in several brain regions of subjects with Autism Spectrum Disorders. Since a number of reports have documented presence of vocal and neuromotor abnormalities in patients with autism and suggested that these dysfunctions predate the onset of the syndrome, we performed a fine-grain characterization of the neonatal vocal and motor repertoire in reelin mutant mice to explore the developmental precursors of the disorder. Our findings evidence a general delay in motor and vocal development in heterozygous (50% reduced reelin) and reeler (lacking reelin gene) mutant mice. As a whole, an increased number of calls characterized heterozygous pup's emission. Furthermore, the typical ontogenetic peak in the number of calls characterizing wild-type pups on postnatal day 4 appeared slightly delayed in heterozygous pups (to day 6) and was quite absent in reeler littermates, which exhibited a flat profile during development. We also detected a preferential use of a specific call category (two-components) by heterozygous and reeler mice at postnatal days 6 and 8 as compared to their wild-type littermates. With regard to the analysis of spontaneous movements, a differential profile emerged early in development among the three genotypes. While only slight coordination difficulties are exhibited by heterozygous pups, all indices of motor development appear delayed in reeler mice. Overall, our results evidence a genotype-dependent deviation in ultrasonic vocal repertoire and a general delay in motor development in reelin mutant pups.